Polycyclic Aromatic Hydrocarbons in Mussel from Iceland: Food safety and environmental aspect - Berglind Ósk Alfreðsdóttir 1987- (2014)
Polycyclic aromatic hydrocarbons (PAHs) are a substance of great environmental and health concern as they can find their way to the human food chain through the ocean’s ecosystem. PAHs are a group of compounds that are composed of fused aromatic rings formed through the combustion of organic matter. The US Environmental Protection Agency (US-EPA) has identified 16 PAHs of particular importance due to their toxicity as priority pollutants. These are the PAHs most commonly used in monitoring projects to gather information and assess the status of food products regarding undesirable substances. The aim of this master thesis was to investigate temporal trends of PAHs in the Icelandic coastal environment in the timeframe 1992-2011. The importance of monitoring the PAHs is twofold: with regard to food safety since they can have mutagenic/carcinogenic effects on humans and from the environmental aspect because they can provide evidence of human activity in the area. Three locations, Brekka in Mjóifjörður, Úlfsá in Skutulsfjörður and Hvassahraun in Hafnarfjörður, were chosen as investigation sites and blue mussels (Mytilus edulis) were chosen as a monitoring species. Extraction of PAHs in the blue mussels were performed by using microwave-assisted extraction followed by solid phase extraction clean up. Identification and quantification was performed with gas chromatograph coupled to a mass spectrometer (GC-MS). In this thesis, the sum of the concentration of the 16 PAHs is expressed as Σ16PAH. The results showed that the concentration in Hvassahraun is relatively low and stable during the time period, with a maximum of Σ16PAH concentration 345 ng/g d.w in the year 1997. In Úlfsá, the concentration was also generally low and stable during the time period, with a maximum of Σ16PAH concentration of 264 ng/g d.w. collected in 2000. The temporal trend in Mjóifjörður showed an increase in PAHs concentration during the time period. The concentration increased in the year 2000, and again between 2007 and 2010, with the highest ...